Changes of Peel Essential Oil Composition of Four Tunisian Citrus during Fruit Maturation - Soumaya Bourgou; Fatma Zohra Rahali; Iness Ourghemmi; Moufida Saïdani Tounsi (The Scientific World Journal)
The present work investigates the effect of ripening stage on the chemical composition of essential oil extracted from peel of four citrus: bitter orange (Citrus aurantium), lemon (Citrus limon), orange maltaise (Citrus sinensis), and mandarin (Citrus reticulate) and on their antibacterial activity. Essential oils yields varied during ripening from 0.46 to 2.70%, where mandarin was found to be the richest. Forty volatile compounds were identified. Limonene (67.90–90.95%) and 1,8-cineole (tr-14.72%) were the most represented compounds in bitter orange oil while limonene (37.63–69.71%), β-pinene (0.63–31.49%), γ-terpinene (0.04–9.96%), and p-cymene (0.23–9.84%) were the highest ones in lemon. In the case of mandarin, the predominant compounds were limonene (51.81–69.00%), 1,8-cineole (0.01–26.43%), and γ-terpinene (2.53–14.06%). However, results showed that orange peel oil was dominated mainly by limonene (81.52–86.43%) during ripening. The results showed that ripening stage influenced significantly the antibacterial activity of the oils against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. This knowledge could help establish the optimum harvest date ensuring the maximum essential oil, limonene, as well as antibacterial compounds yields of citrus.